STUDY OF OPEN-AIR MUSEUM ON KAYUTANGAN STREET CORRIDOR - Cindy Elena Kartika; Lilianny Sigit Arifin (DIMENSI (Journal of Architecture and Built Environment), 2021)
The Kayutangan Corridor is one of the areas in Malang that holds many historical values, namely as a shopping center in the Dutch colonial era. However, the glory and history of kayutangan began to fade with the times. This research's general objective is to provide a design proposal for the Kayutangan corridor that can present historical stories of the buildings along the corridor, such as an open-air museum, with the building as its object. The research method used is descriptive qualitative research with a signage theory approach. The final result of this study is the proposed signage and pedestrian design in the Kayutangan corridor.